2013
DOI: 10.3109/13693786.2012.756989
|View full text |Cite
|
Sign up to set email alerts
|

TheaspHSgene as a new target for detectingAspergillus fumigatusduring infections by quantitative real-time PCR

Abstract: Invasive aspergillosis (IA) is a serious nosocomial infection caused by Aspergillus spp. which has a high mortality rate due to the fact, among other factors, that it is difficult to diagnose. Within the Aspergillus genus, A. fumigatus is the main species causing IA. We propose a virulence factor, the aspHS gene, as a novel target for the specific detection of A. fumigatus by quantitative real-time PCR (qPCR). This target gene encodes a haemolysin, which is overexpressed in vivo during infection. We have desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, the rDNA sequences are highly conserved in nature as well, so they are more suitable for fungal detection in general, or for Aspergillus genus detection, and they cannot distinguish between different species. The product of the aspHS gene is an aegerolysin that is overexpressed in vivo during infection, and it has been proposed as a novel target for specific detection of A. fumigatus by quantitative real-time PCR (Abad-Diaz- de-Cerio et al 2013). In combination with the DNA extraction method, this method can detect A. fumigatus with high specificity.…”
Section: Aegerolysin Genes As Markers In Diagnosis Of Fungal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rDNA sequences are highly conserved in nature as well, so they are more suitable for fungal detection in general, or for Aspergillus genus detection, and they cannot distinguish between different species. The product of the aspHS gene is an aegerolysin that is overexpressed in vivo during infection, and it has been proposed as a novel target for specific detection of A. fumigatus by quantitative real-time PCR (Abad-Diaz- de-Cerio et al 2013). In combination with the DNA extraction method, this method can detect A. fumigatus with high specificity.…”
Section: Aegerolysin Genes As Markers In Diagnosis Of Fungal Diseasesmentioning
confidence: 99%
“…Furthermore, this method can distinguish between nongerminating conidia, where the aegerolysin is not detected, and germinating conidia, where the aegerolysin is detected, which can thus indicate the initiation of infection. AbadDiaz- de-Cerio et al (2013) suggested that these techniques can be sufficiently sensitive and rapid to help clinicians in earlier diagnosis, although the presence of PCR inhibitors in clinical samples like human bronchoalveolar lavage fluids needs to be addressed.…”
Section: Aegerolysin Genes As Markers In Diagnosis Of Fungal Diseasesmentioning
confidence: 99%
“…Single-copy genes have also been used as molecular markers in the diagnosis of IA, which provide a greater specificity to the assay but a lower sensitivity. The single-copy genes that have been used include aspHS, SCW4 and anxC4, which have shown promising results for detecting A. fumigatus, A. flavus, A. niger, A. nidulans, A. terreus and A. versicolour in BAL samples [93,101,106]. Because the aspHS gene encodes a haemolysin that is overexpressed in vivo during infection, its detection provides specificity to differentiate an active infection (germinated conidia) from a non-active one (non-germinated conidia) [101].…”
Section: Molecular Marker or Amplification Targetsmentioning
confidence: 99%
“…The commercially available Myconostica MycAssay Aspergillus PCR, targeting the 18S rRNA gene, is a real-time PCR with promise for detection of Aspergillus DNA in respiratory tract samples, but there are no reports yet in serum or blood [8]. Using a different genetic target, real-time PCR detection of aspHS , encoding for an A. fumigatus –secreted hemolysin, afforded detection in murine samples but unfortunately not consistently in clinical bronchoalveolar lavage samples due to inhibitors [9].…”
Section: Does Pcr Improve Diagnosis?mentioning
confidence: 99%